Effect of radiation intensity on the outcome of postharvest UV-C treatments - Cote, Sandra (2013)
Studies on the use of UV-C radiation of fresh produce have focused on the selection of appropriate doses (energy per unit area) for different commodities, but little attention has been placed on the effect of radiation intensity (dose per unit time). In this study, tomatoes (Solanum lycopersicum cv. Elpida) and strawberries (Fragaria×ananassa cv. Camarosa), were harvested (breaker and 100% of surface red color respectively) and treated with 4kJm-2 of UV-C, at low (3Wm-2) or high (33Wm-2) radiation intensities. Untreated fruits were used as controls. After the treatments and at different storage times the incidence of postharvest rots and the changes in fruit physical and chemical properties were determined. UV-C treatments reduced decay, with the effects being were more marked in fruit exposed to high intensities. Mold counts were unaffected by the treatments, suggesting that improved disease control did not result from greater germicide effect. In both fruit species exposure to UV-C radiation delayed ripening, evidenced as lower color development, pigment accumulation and softening. UV-C-treated fruit maintained better quality than the control. In strawberry, high intensity treatments were more effective to prevent deterioration than in tomato where the differences between UV-C treatments were subtler. Soluble solids, titratable acidity and ethanol soluble antioxidants were not affected regardless of the UV-C intensity. Consumer tests showed higher preference of fruit treated at high UV-C intensity. Results show that in addition to the applied dose, radiation intensity is a main factor determining the effectiveness of UV-C treatments and should not be over-sighted. For a given dose, increasing radiation intensity may in some cases maximize the benefits of UV-C on fruit quality, while significantly reducing the treatments time.